The effects of processing and sequence organization on the timing of turn taking: a corpus study - Roberts, Seán G.; Torreira, Francisco; Levinson, Stephen C. (Frontiers in Psychology, 2015)
The timing of turn taking in conversation is extremely rapid given the cognitive demands on speakers to comprehend, plan and execute turns in real time. Findings from psycholinguistics predict that the timing of turn taking is influenced by demands on processing, such as word frequency or syntactic complexity. An alternative view comes from the field of conversation analysis, which predicts that the rules of turn-taking and sequence organization may dictate the variation in gap durations (e.g., the functional role of each turn in communication). In this paper, we estimate the role of these two different kinds of factors in determining the speed of turn-taking in conversation. We use the Switchboard corpus of English telephone conversation, already richly annotated for syntactic structure speech act sequences, and segmental alignment. To this we add further information including Floor Transfer Offset (the amount of time between the end of one turn and the beginning of the next), word frequency, concreteness, and surprisal values. We then apply a novel statistical framework (“random forests”) to show that these two dimensions are interwoven together with indexical properties of the speakers as explanatory factors determining the speed of response. We conclude that an explanation of the of the timing of turn taking will require insights from both processing and sequence organization.